Analisis Daya Prototipe Superkapasitor Berbasis N-Glc dan Elektrolit Na2SO4 - Jonatan Hutapea; Nur Rohmat; Hasky Bambang Kurniawan (Pusat riset dan Inovasi Nasional, 2026)
The increasingly complex global energy problem drives the need for efficient, low-cost, and environmentally friendly energy storage systems. This study aims to analyze the power performance of two symmetric supercapacitor prototypes using Nitrogen-doped Graphene-Like Carbon (N-GLC) as the electrode material and 1 M as the electrolyte, with different electrode substrates: aluminum and copper. Both prototypes were tested through charging and discharging processes using resistive loads of 470 ohms and 560 ohms for 5 minutes. The analyzed parameters include voltage, current, power, and output energy. The results show that the aluminum electrode achieved a higher maximum charging power of up to 18 mW; however, its energy discharge efficiency was very low at only 0.87%. In contrast, the copper electrode demonstrated a more balanced charging and discharging performance with an energy discharge efficiency of 19.4%. Analysis also indicates that the copper substrate maintains better voltage stability after 6 hours of storage compared to aluminum, which experienced significant degradation. Thus, the copper electrode is superior in maintaining the power and stability of a simple N-GLC-based symmetric supercapacitor system.